Histopathological Study of Psoriasis and Its Grading According to Trozak Scoring System - Vashist, Neelu; Sharma, Ila; Sharma, Mukul (Annals of Pathology and Laboratory Medicine, 2019)
Background: Psoriasis is a chronic papulosquamous disorder of undefined etiology, occuring in 0.09 to 11.4% population. Different clinical types occur with varying histopathology. Early and Late onset psoriasis have been defined based on age at presentation. Methods: Cases diagnosed as Psoriasis, both clinically and histologically, were examined for the individual features of Psoriasis. Histomorphological grading of the lesions was also done using the Trozak scoring system. Result: The mean age of the patients was 42.26 with a male predominance (M:F=3.5: 1). Early onset cases constituted 71% of the total cases, while late onset cases were 29%. The histopathological features were found to be variably present. Acanthosis was observed in 96% cases. Hyperkeratosis (94%), parakeratosis (66%), club shaped rete ridges (88%) with regular elongation of rete ridges (72%) with, suprapapillary plate thinning (74%), hypogranulosis (72%), elongation and edema of dermal papillae (88%) were other features seen in majority of cases. Perivascular mononuclear infiltrate in upper dermis of papillae (76%), dermal (76%) and epidermal (78%) neutrophils, spongiform pustules of Kogoj (24%), Munro’s microabscess (28%), were the inflammatory changes observed, present to a greater extent in the early onset cases than the late onset cases. The Trozak scoring system gave an average score of 9.44, with no significant difference in the early and late onset cases of Psoriasis. Conclusion: Entirely typical histological features are found only in a small percentage of biopsy specimens, even if only clinically typical lesions of psoriasis are examined.